Performance Analysis And Design Of A WDM Ring Network - Dambul, Katrina D. (2007)
The transmission limitations studied in this work that could degrade the performance of a multi-channel WDM ring network are amplified spontaneous emission noise (ASE) arising from the use of Erbium-doped fiber amplifiers (EDFAs), linear crosstalk caused by device imperfections and nonlinear effects such as four mixing (FWN) and cross phase modulation (XPM) due to optical fiber imperfections.